Sejarah Perkembangan Pendidikan Islam di Nusantara: Studi Literatur Tentang Pondok Pesantren dan Madrasah - Eva Nurazizah; Gita Astria; Faelasup Faelasup (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
The article discusses about history and development of two main Islamic educational institutions in Indonesia, Islamic boarding schools and madrasahs are well-known educational institutions in the Islamic tradition. Islamic boarding schools, in particular, have existed as traditional institutions since the early period of Islam's spread throughout the Indonesian archipelago, with a dormitory-based education system and teaching of yellow books. Meanwhile, madrasahs emerged as a response to the need for more systematic and structured Islamic education, especially during the period of Islamic renewal and colonialism. Through a historical-descriptive approach. This paper examines the developmental trajectories and growth dynamics of the two institutions, as well as their important roles in shaping the identity and direction of Islamic education in Indonesia. The findings indicate that, despite differences in their educational approaches and systems, Islamic boarding schools and madrasahs function complementarily in fulfilling the roles of religious and social education within the community.